The history of the tree sparrow in Japan by Fumio Taguchi - Baker, Helen (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
This is a most unusual book. The initial text in in Japanese, followed by a rather shorter English version, with 26 pages full of small colour illustrations and finally many pages of notes, the majority in Japanese but with some English translations. This review is based solely on the English text as I have no knowledge of Japanese. The book is written in an informal, conversational style which is perhaps a little unusual in a hard-back book and the author takes a very personal approach to the subject. His English is a little idiosyncratic but the meaning is usually apparent and I found it quite easy to read.
Keywords: wróblowe; ornitologia; recenzje